The structural basis of nuclear function. - Jackson, D; Cook, P (1995)
Most models for transcription and replication involve polymerases that track along the template. We review here experiments that suggest an alternative in which polymerization occurs as the template slides past a polymerase fixed to a large structure in the eukaryotic nucleus--a "factory" attached to a nucleoskeleton. This means that higher-order structure dictates how and when DNA is replicated or transcribed.